Program Penerapan Kitab Syifa’ul Jinan Dalam Pembelajaran Al-Qur’an Untuk Mengembangkan Kemampuan Baca Al-Qur’an Anak Desa Sumber Kepuh Butuh Kras Kediri - Laili Khusna Kurin; Khoirotul Izzah (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2020)
The learning of the Qur'an is the most important lesson, because when a person is wrong in his pronunciation it will be destructive to its meaning. In this case, the researchers applied tajwid science referred to from the book of Shifaul Jinan which is the basis of tajwid science. The purpose of this research is to apply the book of Shifaul Jinan in the study of the Qur'an and develop the ability to read the Qur'an in the children of The Village Of Kepuh Source Needs Kras Kediri. The results of this study showed that the learners of the Qur'an in the children of Sumber Kepuh Village Need Kras Kediri has been arranged in accordance with the curriculum of the council of primary and secondary education. In the implementation of learning, teachers teach materials that exist in one basic competency used for two meetings so that the results are maximal. In the first meeting the teacher emphasized the understanding of tajwid science materials and for the second meeting teachers further increased the practice of reading the Qur'an so that the ability to read the Qur'an continues to develop.